IMPACT OF MIGRANT LABOUR AND HUMAN TRAFFICKING ON GLOBAL ECONOMY WITH EMPHASIS ON INDIA - Pandey, Ashok Kumar; Vig, Komal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Migrant labour and human trafficking exert contrasting influences on the global economy. Migrant labours, driven by workers crossing borders or relocating within countries, addresses critical workforce shortages in host economies and channels substantial remittances back home, thereby fostering development. Conversely, human trafficking exploits vulnerable populations for illicit profits, imposing heavy societal costs through enforcement, healthcare burdens, and diminished productivity. Focusing on India, a major exporter of migrant labour and a trafficking nexus; this paper quantifies migration’s economic benefits against the losses wrought by trafficking. India’s 139 million internal migrants and 100 billion in remittances (2022) underscore migration’s economic significance, while trafficking’s estimated annual illicit revenues (30–343 billion) highlight urgent human and financial repercussions . Through comparative analysis, this study underscores the need for strengthened labour protections, targeted anti-trafficking measures, and international cooperation to reconcile economic growth with human rights imperatives.